WILLIAM DAVY AND JOSEPH WHITE’S INTERPRETATION OF TIMUR’S LIFE AND PERSONAL QUALITIES (Scientific journal of the Fergana State University, 2023)
The article contains information about the life and work of Amir Temur, his struggle for the creation of his independent state and the creation of “Temur tuzuklari” by the English authors W.Davy and J.White. The information given by him was compared to the Eastern sources, and the information given in the sources was analized It was noted in the article that the compaigns conducted by Amir Temur were aimed at the freedom and peace of his country. Also, the originality of the information of “Temur tuzuklari” given by the English authors is shown.